White-Light Electroluminescence with Tetraphenylethylene as Emitting Layer of Aggregation-Induced Emissions Enhancement - 罗建芳 王晓宏 王筱梅 苏文明 陶绪堂 陈志刚 (Chinese journal of chemistry, 2012)
Tetraphenylethylene （TPE） based molecules with easy synthesis, good thermal stability, and especially their aggregation-induced emissions enhancement （AIEE） effect recently become attractive organic emitting materials due to their potentially practical application in OLEDs. Herein, the AIEE behaviors of tetraphenylethylene dyes （TMTPE and TBTPE） were investigated. Fabricated luminesent device using TMTPE dye as emitting layer displays two strong emitting bands： the blue emission coming from the first-step aggregation and the yellow emission attrib- uted to the second-step aggregation. Thus, it can be utilized to fabricate the white-light OLEDs （WOLEDs） of the single-emitting-component. A three-layer device with the brightness of 1200 cd·m^-2 and current efficiency of 0.78 cd·A^-1 emits the close to white light with the CIE coordinates of x=0.333 and y=0.358, when applied voltage from 8-13 V, verifying that the TPE-based dyes of AIEE effect can be effectively applied in single-emitting- component WOLEDs fabrication.